Tribology study of aluminum-based foam - Palic, Nikola; Sharma, Varun; Zivic, Fatima; Mitrovic, Slobodan; Grujovic, Nenad (Journal of Production Engineering, 2019)
Closed cell metallic foam prepared from ALUHAB technology has been studied using tribological methodology. The main goal of the study was tribological properties of closed cell porous structure made of aluminium alloy. Tribological testing of the porous Al-based alloy were realised under different low loads: 10 mN, 25 mN, 50 mN, 75 mN, and 100 mN using CSM nanotribometer, with linear reciprocating mode. Ball-on-disc contact geometry was used and dynamic friction coefficient was observed. Results revealed that, friction coefficient exhibited large fluctuations in values under different loads, from moderate friction coefficient (0.2 at 100 mN load) up to the very high values (1.4 at 25 mN load). Under very small loads (10 mN) it was hard to get reliable results due to porosity influence and extremely high friction coefficient values were obtained.